Early stages of clastic deposition in the Most Basin (Ohre Rift, Czech Republic, Early Miocene): timing and possible controls - Matys Grygar, T. (Tomáš); Mach, K.; Hošek, M. (Michal); Schnabl, P. (Petr); Martinez, M.; Koubová, M. (Bulletin of Geosciences, 2017)
This study examines the early stages of clastic deposition above the main coal seam in the Most Basin (Ohre Rift, NW Czech Republic). Eight drill cores were subjected to chemical analysis by X-ray fluorescence spectroscopy (XRF) and cation exchange capacity determination (CEC) to corroborate the local chemostratigraphic scheme and extend its temporal and spatial ranges. Additionally, four drill cores were subjected to palaeomagnetic polarity analysis for magnetostratigraphic dating, and two cores were subjected to the frequency analysis of variations in elemental compositions to obtain cyclostratigraphic patterns and more detailed insight into depositional dynamics. We demonstrate that a local lake was present in the Bilina area from the end of palaeomagnetic chron C5Er through chron C5En (18.524-18.056 Ma according to the Astronomically Tuned Neogene Time Scale 2012) to the beginning of the C5Dr chrons. This finding extends the previous age models for the Most Formation by more than 0.5 My (18.6 to 17.9 Ma). The chemostratigraphic scheme, which is based on variations in the concentrations of K and the values of CEC, was successfully extended from the basin centre to its north-east periphery, which reflects the basin-wide environmental changes that terminated the peat accumulation (coal formation) in the basin. The basin-wide lacustrine body formed by the coalescence of local lakes and the flooding of the remaining peatlands ca. 17.8 Ma (during C5Dn), which is coeval with the substantial reduction of the Antarctic ice sheet prior to the onset of the Miocene climatic optimum (MCO). The Most Basin deposits are the most detailed (with respect to temporal resolution) continental sedimentary archive of the time period preceding the MCO that have not been described to date.